Primary Cilia in Glial Cells: An Oasis in the Journey to Overcoming Neurodegenerative Diseases - Ki, Soo Mi; Jeong, Hui Su; Lee, Ji Eun (Frontiers in Neuroscience, 2021)
Many neurodegenerative diseases have been associated with defects in primary cilia, which are cellular organelles involved in diverse cellular processes and homeostasis. Several types of glial cells in both the central and peripheral nervous systems not only support the development and function of neurons but also play significant roles in the mechanisms of neurological disease. Nevertheless, most studies have focused on investigating the role of primary cilia in neurons. Accordingly, the interest of recent studies has expanded to elucidate the role of primary cilia in glial cells. Correspondingly, several reports have added to the growing evidence that most glial cells have primary cilia and that impairment of cilia leads to neurodegenerative diseases. In this review, we aimed to understand the regulatory mechanisms of cilia formation and the disease-related functions of cilia, which are common or specific to each glial cell. Moreover, we have paid close attention to the signal transduction and pathological mechanisms mediated by glia cilia in representative neurodegenerative diseases. Finally, we expect that this field of research will clarify the mechanisms involved in the formation and function of glial cilia to provide novel insights and ideas for the treatment of neurodegenerative diseases in the future.